Water Absorption of Chitosan, Collagen, and Chitosan/Collagen Blend Membranes Exposed to Gamma-Ray Irradiation: Water Absorption of the Membranes Exposed to Irradiation - Fajar Lukitowati; Decky Joesiana Indrani (Iranian Journal of Pharmaceutical Sciences, 2018)
This study investigated the water absorption of chitosan, collagen, and chitosan/collagen blend membranes exposed to gamma-ray irradiation. These membranes were produced via the solvent evaporation method. All membranes then underwent irradiation at 15 or 25 kGy gamma-ray doses, while membranes without irradiation were used as controls. After immersing the membranes in distilled water for up to 180 min, water absorption was determined by calculating the percentage weight increase. The results demonstrated some changes in the water absorption curves with differing membranes and irradiation doses. However, after 60 min, all of the water absorption curves plateaued. With respect to membrane type, the chitosan membranes exhibited the highest water absorption; the blend displayed the lowest; and also the collagen was in the mid range. With the use of higher radiation doses, the chitosan membranes displayed lower water absorption, which was also true of the blend but not collagen membranes. To conclude, the water absorption of chitosan, collagen, and chitosan/collagen blend membranes with and without gamma-ray irradiation initially increased steadily and then plateaued. The water absorption values of the irradiated blend membranes were the lowest; however, the values were relatively steady.